Point of care detection of anemia in non-invasive manner by using image processing and convolutional neural network with mobile devices - Rahman, Md. Nafis Nakib; Sadik, Saif Abdullah; Biswas, Anindya; Tazul, Ratul Bin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.